Perancangan Konten Instagram untuk Mempromosikan Roti Bakar Full Senyum - Shasha Bedys Fazhiera; Farkhan Alfi Abdul Rasyid; Riftya Sandy (Jurnal Hukum, Administrasi Publik dan Negara, 2024)
This study aims to design an effective Instagram content strategy as a promotional medium for Full Smile Roti Bakar products. This toast is known for its unique taste and attractive presentation, and the aim of this research is to attract the attention of potential audiences and increase interactions and followers on social media platforms. The research method used is analysis of Instagram content from similar competitors, as well as the implementation of visual and narrative techniques to create an interesting and informative feed. It is hoped that the results of this research can provide practical guidance for small business owners or startups in utilizing social media to increase visibility and sales.